Exciton‐Vibrational Couplings in Homo‐ and Heterodimer Stacks of Perylene Bisimide Dyes within Cyclophanes: Studies on Absorption Properties and Theoretical Analysis. Issue 42 (9th September 2016) - Bialas, David; Brüning, Christoph; Schlosser, Felix; Fimmel, Benjamin; Thein, Johannes; Engel, Volker; Würthner, Frank
Abstract: The optical properties of a series of three cyclophanes comprising either identical or different perylene bisimide (PBI) chromophores were studied by UV/Vis absorption spectroscopy and their distinctive spectral features were analyzed. All the investigated cyclophanes show significantly different absorption features with respect to the corresponding constituent PBI monomers indicating strong coupling interactions between the PBI units within the cyclophanes. DFT calculations suggest a π‐stacked arrangement of the PBI units at close van der Waals distance in the cyclophanes with rotational displacement. Simulations of the absorption spectra based on time‐dependent quantum mechanics properly reproduced the experimental spectra, revealing exciton‐vibrational coupling between the chromophores both in homo‐ and heterodimer stacks. The PBI cyclophane comprising two different PBI chromophores represents the first example of a PBI heterodimer stack for which the exciton coupling has been investigated. The quantum dynamics analysis reveals that exciton coupling in heteroaggregates is indeed of similar strength as for homoaggregates. Abstract : Dyes/pigments : The absorption properties of a series of three cyclophanes comprising either the same or different perylene bisimide (PBI) dyes have been studied. All cyclophanes exhibit different absorption features with respect to the corresponding constituent monomeric dyes (see figure).